Reflections on a Phenomenological Ethics: Its Foundations on Empathy and the Acknowledgement of Vulnerability - Breuer, Irene (Bollettino Filosofico, 2022)
This paper reflects on the possibility of phenomenological ethics that grounds on the acknowledgment of our ontological/situational vulnerability, to which migrants and exiled people are particularly exposed. I argue that such an ethics, while being both universal and particular and guided by reason, has its foundation in affectivity. By taking recourse on both Husserl’s late ethics and the ethical approaches of J. Butler, M.A. Fineman, A. MacIntyre, M.C. Nussbaum and B. Waldenfels. I’ll argue that a proper recognition of our bodily vulnerability and the concomitant absolute value of self-preservation involves both a proper material axiology and the cultivation of emotions and virtues, such as love and solidarity, within a community bound by love, reason and the pursuit of happiness. Keywords: Affectivity, Exile, Phenomenological Ethics, Self-preservation, Vulnerability